Experimental and analytical study on electro-osmosis in low-permeability soil considering the pore size effect. Issue 2 (6th February 2021) - Zhou, Haijun; Fang, Yingguang; Chen, Minghua; Gu, Renguo; Li, Wei
Abstract : Existing electro-osmotic calculation models are mostly based on the assumption of a porous medium with uniform pores, whereas natural soil has pores of different sizes. This is especially significant in the case of low-permeability soil, whose pore size can vary over five or six orders of magnitude, from the nanometre to the millimetre scale. Experimental results have revealed significant differences in the electro-osmotic flow characteristics of soils with various pore sizes, indicating a strong dependence on pore size distribution (PSD). This dependence is termed the pore size effect (PSE) on electro-osmosis. In this paper, a series of one-dimensional electro-osmosis experiments on three types of low-permeability clay soil are conducted to quantify the PSE on electro-osmosis. Based on the experimental results and an analysis of electro-osmotic characteristics, a modified analytical approach considering the actual soil PSD and its effect on electro-osmosis is proposed and thereby two modified analytical models are established. Using the experimental results, the modified models are compared with the existing Helmholtz–Smoluchowski model and other models that assume uniform pores. The results show that the PSE increases with increasing thickness of the electric double layer and that the modified models can be used to reasonably calculate the electro-osmotic permeability of low-permeability soil.